Implementation of Facility Management to develop Education Quality - Asep Mumung; Iim Wasliman; Ikka Kartika; Ida Tedjawiani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
The success of educational programs in schools is strongly influenced by the condition of educational facilities and infrastructure. Fulfilling the need for infrastructure facilities aims to describe and analyze planning, organizing, mobilizing, monitoring, as well as supporting and inhibiting factors for infrastructure management to develop the quality of education at RA Nurul Iman Majalengka. Qualitative research data collection techniques by means of observation, interviews, documentation and triangulation. Data analysis techniques: data collection, data reduction, data presentation and drawing conclusions. The findings of this research are planning with annual meetings, evaluating, reviewing work programs, implementing program activities and socializing the program to parents. Organizing: organizational structure, staffing, job descriptions and responsibilities, communication and coordination. Movement by procuring goods, inventory, maintenance, selection, reporting. Supervision by conducting evaluation and supervision as well as follow-up from supervision. Supporting factors: good design, employee placement, neat filing and involvement of madrasa supervisors. Inhibiting factors: the commitment of each human resource, lack of funds, complicated regulations and lack of employee skills development.